Implementasi Supervisi Akademik Dalam Meningkatkan Kualitas Pembelajaran di SMA dan SMK Se-Kecamatan Abung Semuli Lampung Indonesia - M. Ihsan Dacholfany; Nining Surya Ningsih; Sudirman Aminin (El-Ghiroh : Jurnal Studi Keislaman, 2020)
Motivated by the problems of the quality of learning. To improve the quality of teaching carried out by teachers, through educational supervision. The research was conducted in SMA and SMK in Abung Semuli Subdistrict, Lampung which aims to describe the Principal's knowledge regarding the role of supervisor and to know the Implementation of Academic Supervision in Improving the Quality of Teacher Learning. Research using a qualitative research approach with phenomenological theory. Conclusions: Principals of SMA and SMK in Abung Semuli District, Lampung have good knowledge of academic supervision as evidenced by the supervision of these schools. Implementation of Academic Supervision in Improving the Quality of Learning Indonesian language teachers using individual techniques in the form of class visits begins with making a supervision program containing planning, preparation, implementation, evaluation.